THE RELATIONSHIP OF PREGNANT WOMEN CLASS ACTIVITIES TO PREGNANT MOTHERS' READINESS IN FACING LABOR AT THE PUSKESMAS BANGUN REJO VILLAGE, DELI REGENCY, SERDANG IN 2021 - Ginting, Siska; Sinuhaji, Lydia; Sinaga, Martaulina; Munthe, Juliana; Azizah, Nur; Marliani, Marliani; Asia, Mutiara (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2022)
Pregnant women class is a study group for pregnant women who get various health information and pregnancy exercises in preparing for childbirth. The number of pregnant women participating in the Maternity Class is 40 people. They do not prepare for childbirth because they feel that they do not need to be prepared in the face of childbirth. The purpose of the study was to determine the relationship between pregnancy exercise class activities and the preparation of pregnant women in preparation for childbirth. This type of research is analytical with a cross sectional approach. The population was 40 pregnant women who took part in the class of pregnant women and all of them were used as research samples. Data were analyzed bivariately using the chi square test at a significance level of 95%. The results showed that pregnant women carried out various activities in the class for pregnant women with the highest frequency in the less category 23 people (57.5%) and 25 people were not ready to give birth (62.5%). There is a relationship between pregnancy exercise class activities with the readiness of pregnant women in facing childbirth (p 0.039 <0.05). It is hoped that the Puskesmas will optimize the implementation of classes for pregnant women through various innovative and interesting activities that can make pregnant women feel at home in participating in pregnancy exercise classes from start to finish.